Low Dose Growth Hormone Adjuvant Treatment With Ultra-Long Ovarian Stimulation Protocol in Poor Responders Showed Non-inferior Pregnancy Outcome Compared With Normal Responders - Lee, Yi-Xuan; Shen, Meng-Shun; Tzeng, Chii-Ruey (Frontiers in Endocrinology, 2019)
Background: Growth hormone (GH) has long been used as adjuvant treatment in ovarian stimulation for in vitro fertilization (IVF), especially in poor responder (PR) patients. However, its clinical efficacy remains unclear, and most studies are underpowered owing to their small sample size with different regimens. Methods: Our study was divided into two parts. The first part was a parallel randomized, observational study in which 184 patients who fulfilled the criteria of poor ovarian response (POR) were enrolled and received ultra-long ovarian stimulation protocol with or without GH adjuvant therapy. For the second part, clinical data were retrospectively extracted from 163 patients classified as PRs who received 10 IU GH adjuvant therapy and 157 patients classified as normal responders (NRs) who received the same IVF protocol treatment without GH adjuvant therapy. Results: For the first part of the study, the ovarian response, the number of oocytes retrieved, and the number of available embryos transferred were all significantly higher in the GH (+) group than in the GH (–) group. The clinical pregnancy rate was significantly higher in the GH (+) group (31.9 vs. 16.7%, p = 0.0168). The miscarriage rate did not differ significantly between the groups. The ongoing pregnancy rate was also significantly higher in the GH (+) group than in the GH (–) group (26.6 vs. 14.4%, p = 0.0418). Logistic regression revealed that the chance of clinical pregnancy in the GH (+) group significant increased 2.34-fold in comparison with the GH (–) group (p = 0.018). Subgroup analysis showed that the chance of clinical pregnancy in the GH (+) group significantly increased 2.38-fold (p = 0.034). The second part of the study showed no statistical difference between the PR with GH and the NR without GH groups regarding the implantation rate (15.6 vs. 19.8%, p = 0.3254) and the clinical pregnancy rate (31.9 vs. 39.5%, p = 0.1565). The NR without GH group showed insignificantly higher chance of clinical pregnancy (OR = 1.39, p = 0.157) compared with the PR with GH group. Conclusion: Our results suggested that low-dose GH supplementation may improve ovarian response and pregnancy outcome in POR patients, particularly in patients younger than 40 years old. Moreover, the low-dose GH effect in POR patients resulted in non-inferior clinical pregnancy outcome compared with NRs.